2010
DOI: 10.1890/09-0478.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity of soil carbon fractions in boreal forest soil

Abstract: Abstract. Feedback to climate warming from the carbon balance of terrestrial ecosystems depends critically on the temperature sensitivity of soil organic carbon (SOC) decomposition. Still, the temperature sensitivity is not known for the majority of the SOC, which is tens or hundreds of years old. This old fraction is paradoxically concluded to be more, less, or equally sensitive compared to the younger fraction. Here, we present results that explain these inconsistencies. We show that the temperature sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 30 publications
3
62
0
1
Order By: Relevance
“…The temperature sensitivity of peat mineralization, as expressed by its Q 10 value, is a useful parameter for characterizing the intrinsic decomposability of SOM (Hogg et al, 1992;Biasi et al, 2005;Davidson and Janssens, 2006;Conant et al, 2008;Boddy et al, 2008;Karhu et al, 2010;Hilasvuori et al, 2013). In line with the biochemical and elemental evidence reviewed above, it was reported to increase with increasing resistance of peat soils against OM decomposition (Scanlon and Moore, 2000), soil depth and peat age (Hardie et al, 2011;Hilasvuori et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…The temperature sensitivity of peat mineralization, as expressed by its Q 10 value, is a useful parameter for characterizing the intrinsic decomposability of SOM (Hogg et al, 1992;Biasi et al, 2005;Davidson and Janssens, 2006;Conant et al, 2008;Boddy et al, 2008;Karhu et al, 2010;Hilasvuori et al, 2013). In line with the biochemical and elemental evidence reviewed above, it was reported to increase with increasing resistance of peat soils against OM decomposition (Scanlon and Moore, 2000), soil depth and peat age (Hardie et al, 2011;Hilasvuori et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…The Q 10 values observed in this experiment were low (all less than 2.0, even when controlling for changes in soil moisture). Temperature sensitivities of ∼ 2 are more typical (Dutta et al, 2006;Schädel et al, 2016), although the temperature sensitivity of C release can change over time of incubation (Dutta et al, 2006) and vary between soil fractions cycling over different time horizons (Karhu et al, 2010;Schädel et al, 2014). Observed surface CO 2 fluxes at this CPCRW site exhibited a Q 10 of 5.1 ± 1.4 over a temperature range of 3.5-15 • C (C. Anderson, personal communication, 2016); however, these surface fluxes were measured over multiple months and include root respiration preventing any direct comparison.…”
Section: Temperature Vs Moisture Sensitivity For Cumulative Emissionsmentioning
confidence: 99%
“…Soils isolated during incubation may, for example, underestimate temperature sensitivity of respiration (Podrebarac et al, 2016) or exhibit lag effects . It should also be noted that our 100-day incubation was not long enough to observe slowly cycling soil fractions, which may vary in their response to experimental manipulation (Karhu et al, 2010). Nonetheless, the controlled environments of incubations provide an important way to elucidate the key mechanisms controlling GHG from high-latitude soils .…”
Section: Limitations and Weaknessesmentioning
confidence: 99%
“…Previous studies have shown that Q 10 variations are closely related to soil temperature (Kirschbaum, 2006;Von Lutzow and Kogel-Knabner, 2009), substrate availability (Ågren and Wetterstedt, 2007;Gershenson et al, 2009), substrate quality (Von Lutzow and Kogel-Knabner, 2009;Sakurai et al, 2012), and the size and composition of a microbial population (Djukic et al, 2010;Karhu et al, 2010). Soil moisture is the most significant limiting factor for underground physiological processes in dry and semi-dry ecosystems (Balogh et al, 2011;Cable et al, 2011;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is an issue of considerable debate Kirschbaum, 2006), and the variations in Q 10 are the main source of controversy on this feedback intensity (Larionova et al, 2007;Karhu et al, 2010;Conant et al, 2011;Sakurai et al, 2012). Therefore, understanding the factors influencing Q 10 is important to accurately estimate C cycle and the feedback from the expected warmer climate.…”
Section: Introductionmentioning
confidence: 99%